Pengaruh Karakteristik Perusahaan, Good Corporate Governance (GCG), dan Corporate Social Responsibility (CSR) terhadap Penghindaran Pajak (Tax Avoidance) - Aditya Kusuma Wardani; Eva Anggra Yunita; Amirah Amirah (Faculty of Economics and Business, University of Pancasakti Tegal, 2016)
This study aims to explain the effect simultaneously and partially of the variable firm size, leverage, capital intensity, audit committee, independent commissioner and CSR on tax avoidance. Data collection of this study using secondary data. Deep population this research is a food and beverage company. While the sample in this study is a food and beverage company listed on the Stock Exchange in 2014-2016, which amounted to 11 companies. In this case the financial statements of the company, which amounted to 33 financial statement data. The results showed that simultaneously the size of the company, leverage, capital intensity, audit committee, independent commissioner and CSR had a significant effect on tax avoidance. Firm size, leverage, capital intensity, and CSR simultaneously have a significant effect on tax avoidance. While the audit committee and independent commissioners simultaneously have no effect on tax avoidance